CYBERJUSTICE: THE MEDIATOR’S CONCILIATORY ACTIVITY BETWEEN TECHNIQUE AND TECHNOLOGY - Coppola, Irene (Revista Eletrônica de Direito Processual, 2024)
The objective of this research is to highlight that the subjective role of the legal practitioner, both mediator and judge - within the pre-litigation phase, as well as the litigation phase - appears indispensable in its technical and technological training to arrive at the use of Cyberjustice, understood as a conscious innovation of method.